The Perverse Effects of Job-Security Provisions on Job Security in Italy: Results from a Regression Discontinuity Design - Alexander Hijzen; Leopoldo Mondauto; Stefano Scarpetta (Institute for the Study of Labor (IZA), 2013)
This paper analyses the impact of employment protection (EP) on the composition of the workforce and worker turnover using a unique firm-level dataset for Italy. The impact of employment protection is analyzed by means of a regression discontinuity design (RDD) that exploits the variation in EP provisions across firms below and above a size threshold. Using our RDD approach, we show that EP increases worker reallocation, suggesting that EP tends to reduce rather to increase worker security on average. We further show that this can be entirely explained by the fact that firms facing more stringent EP make a greater use of workers on temporary contracts. Our preferred estimates suggest that the discontinuity in EP increases the incidence of temporary work by 2-2.5 percentage points around the threshold. Moreover, further analysis suggests that the effect of employment protection persists among larger firms well beyond the threshold and may account for about 20% of the overall incidence of temporary work. There is also evidence that EP reduces labour productivity and this effect is to an important extent due to the impact of EP on worker reallocation and the incidence of temporary work.
Keywords: J42; J63; J65; 330; employment protection legislation; worker reallocation; temporary contracts; labour market duality